Can Individualized Learning Plans in an advanced clinical experience course for fourth year medical students foster Self-Directed Learning?. Issue 1 (December 2016) - Chitkara, Maribeth; Satnick, Daniel; Lu, Wei-Hsin; Fleit, Howard; Go, Roderick; Chandran, Latha
Abstract Background Residency programs have utilized Individualized Learning Plans (ILPs) to customize resident education while undergraduate medical education has not done so in a meaningful way. We discuss the use of ILPs within a fourth year medical school course to facilitate self-directed learning (SDL). Methods At Stony Brook University School of Medicine, an ILP component was added to the Advanced Clinical Experience (ACE) course for fourth year students. Each completed an ILP outlining personal learning goals and strategies to achieve them. An adaptation of the Motivated Strategies for Learning Questionnaire (MSLQ) (Duncan T and McKeachie W, Educ Psych 40(2):117-128, 2005 and Cook DA et al., Med Ed 45:1230-1240, 2011) was used to measure success of ILPs in improving SDL. Qualitative data analysis was conducted on the ILPs and self-reflections. Results Forty-eight students participated. Two of the four SDL sub-domains identified on the MSLQ showed improvement; self-efficacy (p  = .001) and self-regulation (p  = .002). 'Medical Knowledge' was the competency most frequently identified as an area of concentration (90 %) and professionalism was selected least frequently (4 %). A higher percentage (83 %) of students who reported complete achievement of their ILP goals also reported feeling better prepared for entering residency. Conclusions ILPs improve SDL strategies among medical students and may serve as useful tools to help shape future learning goals as they transition to residency training.